Exploration of co-sputtered Ta2O5–ZrO2 thin films for gravitational-wave detectors. (13th September 2021) - Abernathy, M; Amato, A; Ananyeva, A; Angelova, S; Baloukas, B; Bassiri, R; Billingsley, G; Birney, R; Cagnoli, G; Canepa, M; Coulon, M; Degallaix, J; et al.
Abstract: We report on the development and extensive characterization of co-sputtered tantala–zirconia (Ta2 O5 -ZrO2 ) thin films, with the goal to decrease coating Brownian noise in present and future gravitational-wave detectors. We tested a variety of sputtering processes of different energies and deposition rates, and we considered the effect of different values of cation ratio η = Zr/(Zr + Ta) and of post-deposition heat treatment temperature T a on the optical and mechanical properties of the films. Co-sputtered zirconia proved to be an efficient way to frustrate crystallization in tantala thin films, allowing for a substantial increase of the maximum annealing temperature and hence for a decrease of coating mechanical loss φ c . The lowest average coating loss was observed for an ion-beam sputtered sample with η = 0.485 ± 0.004 annealed at 800 °C, yielding φ ¯ c = 1.8 × 1 0 − 4 rad. All coating samples showed cracks after annealing. Although in principle our measurements are sensitive to such defects, we found no evidence that our results were affected. The issue could be solved, at least for ion-beam sputtered coatings, by decreasing heating and cooling rates down to 7 °C h −1 . While we observed as little optical absorption as in the coatings of current gravitational-wave interferometers (0.5 parts per million), further development will be needed to decrease light scattering and avoid the formation of defects upon annealing.